PEMBANGUNAN MASYARAKAT DALAM PERSPEKTIF PENYULUHAN - Puji Hardiyanti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
To succeed the national development to achieve its goal, the community participation plays a very strategic role. This article discusses a number of models, methods, and techniques how to motivate the communities as human resources to take part in the development. The models introduced and discussed include Laku and SL-PHT. The strength and the weakness of each model are described thoroughly considering andragogy and continuous learning are the principles in community development.